+0

# Ergebnis

0
873
2

a/(a+b)+a*a/(a*a-b*b)+b/(a-b)=

21.10.2015

### Beste Antwort

#2
+26379
+34

a/(a+b)+a*a/(a*a-b*b)+b/(a-b)=?

$$\begin{array}{lcl} \frac{a}{a+b} +a\cdot \left( \frac{a}{a\cdot a-b\cdot b} \right) +\frac{b}{a-b}&& \\\\ =\frac{a}{a+b} +\frac{a\cdot a}{a\cdot a-b\cdot b} +\frac{b}{a-b} \\\\ =\frac{a}{a+b} +\frac{a^2}{a^2-b^2} +\frac{b}{a-b} \qquad | \qquad \text{3. Binom }~ a^2-b^2 = (a+b)(a-b)\\\\ =\frac{a}{a+b} +\frac{a^2}{(a+b)(a-b)} +\frac{b}{a-b} \\\\ =\frac{a}{a+b} +\frac{a}{a+b} \cdot \frac{a}{a-b} +\frac{b}{a-b} \\\\ =\frac{a}{a+b} \left( 1+ \frac{a}{a-b} \right) +\frac{b}{a-b} \\\\ =\frac{a}{a+b} \left( \frac{a-b+a}{a-b} \right) +\frac{b}{a-b} \\\\ =\frac{a}{a+b} \left( \frac{2a-b}{a-b} \right) +\frac{b}{a-b} \\\\ =\frac{1}{a-b} \left( \frac{a(2a-b)}{a+b} +b \right) \\\\ =\frac{1}{a-b} \left( \frac{a(2a-b)+b(a+b)}{a+b} \right) \\\\ =\frac{a(2a-b)+b(a+b)}{(a-b)(a+b)}\\\\ =\frac{2a^2-ab+ba+b^2}{(a-b)(a+b)} \qquad | \qquad -ab+ba = 0\\\\ =\frac{2a^2+b^2}{(a-b)(a+b)} \qquad | \qquad \text{3. Binom }~ (a+b)(a-b)= a^2-b^2 \\\\ \mathbf{=\frac{2a^2+b^2}{a^2-b^2 }} \\\\ \mathbf{\frac{a}{a+b} +a\cdot \left( \frac{a}{a\cdot a-b\cdot b} \right) +\frac{b}{a-b}=\frac{2a^2+b^2}{a^2-b^2 }} \\\\ \end{array}$$

22.10.2015

#1
+12528
+4

Hier kommt Dein Lösungsweg:

21.10.2015
#2
+26379
+34
Beste Antwort

a/(a+b)+a*a/(a*a-b*b)+b/(a-b)=?

$$\begin{array}{lcl} \frac{a}{a+b} +a\cdot \left( \frac{a}{a\cdot a-b\cdot b} \right) +\frac{b}{a-b}&& \\\\ =\frac{a}{a+b} +\frac{a\cdot a}{a\cdot a-b\cdot b} +\frac{b}{a-b} \\\\ =\frac{a}{a+b} +\frac{a^2}{a^2-b^2} +\frac{b}{a-b} \qquad | \qquad \text{3. Binom }~ a^2-b^2 = (a+b)(a-b)\\\\ =\frac{a}{a+b} +\frac{a^2}{(a+b)(a-b)} +\frac{b}{a-b} \\\\ =\frac{a}{a+b} +\frac{a}{a+b} \cdot \frac{a}{a-b} +\frac{b}{a-b} \\\\ =\frac{a}{a+b} \left( 1+ \frac{a}{a-b} \right) +\frac{b}{a-b} \\\\ =\frac{a}{a+b} \left( \frac{a-b+a}{a-b} \right) +\frac{b}{a-b} \\\\ =\frac{a}{a+b} \left( \frac{2a-b}{a-b} \right) +\frac{b}{a-b} \\\\ =\frac{1}{a-b} \left( \frac{a(2a-b)}{a+b} +b \right) \\\\ =\frac{1}{a-b} \left( \frac{a(2a-b)+b(a+b)}{a+b} \right) \\\\ =\frac{a(2a-b)+b(a+b)}{(a-b)(a+b)}\\\\ =\frac{2a^2-ab+ba+b^2}{(a-b)(a+b)} \qquad | \qquad -ab+ba = 0\\\\ =\frac{2a^2+b^2}{(a-b)(a+b)} \qquad | \qquad \text{3. Binom }~ (a+b)(a-b)= a^2-b^2 \\\\ \mathbf{=\frac{2a^2+b^2}{a^2-b^2 }} \\\\ \mathbf{\frac{a}{a+b} +a\cdot \left( \frac{a}{a\cdot a-b\cdot b} \right) +\frac{b}{a-b}=\frac{2a^2+b^2}{a^2-b^2 }} \\\\ \end{array}$$

heureka 22.10.2015